2012
DOI: 10.1212/wnl.0b013e31825f04d8
|View full text |Cite
|
Sign up to set email alerts
|

Do acute phase markers explain body temperature and brain temperature after ischemic stroke?

Abstract: Objective: Both brain and body temperature rise after stroke but the cause of each is uncertain.We investigated the relationship between circulating markers of inflammation with brain and body temperature after stroke. Methods:We recruited patients with acute ischemic stroke and measured brain temperature at hospital admission and 5 days after stroke with multivoxel magnetic resonance spectroscopic imaging in normal brain and the acute ischemic lesion (defined by diffusion-weighted imaging [DWI]). We measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The mean temperature in the ischaemic area was 38.4 o C and 37.7 o C in the remaining part, while the body temperature oscillated around 36.6 o C. An increased concentration of interleukin 6 correlated with higher temperature of normal brain areas both on admission and after 5 days post-admission. No similar correlation was found with respect to the temperature in the ischaemic area [21].…”
Section: Central Fever In Various Clinical Conditions Head Injurymentioning
confidence: 79%
See 3 more Smart Citations
“…The mean temperature in the ischaemic area was 38.4 o C and 37.7 o C in the remaining part, while the body temperature oscillated around 36.6 o C. An increased concentration of interleukin 6 correlated with higher temperature of normal brain areas both on admission and after 5 days post-admission. No similar correlation was found with respect to the temperature in the ischaemic area [21].…”
Section: Central Fever In Various Clinical Conditions Head Injurymentioning
confidence: 79%
“…Hyperthermia is a common complication of AIS occurring in up to 50% of patients and is associated with a poorer prognosis [19]. The processes determining the brain temperature in AIS have not been fully elucidated [20,21]. Animal studies have demonstrated that under normal health conditions, the balance between the generation of heat in various metabolic processes and cooling of the brain by To facilitate the diagnosis of CF, it is necessary to determine the diagnostic criteria or find the diagnostic markers.…”
Section: Strokementioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, MRSI can detect metabolic changes in strokes [77], autism [78], brain tumors [79], multiple sclerosis [80], seizure [81], depression [82], Parkinson's disease [83], Kimura disease [84], etc. Table 4 lists the identifiable metabolites (N-acetyl aspartate, choline, creatine, lipid, lactate, myoinositol, glutamate and glutamine), and gives their peak positions and indications of change.…”
Section: Other Modalitiesmentioning
confidence: 99%